Self-healing poly(acrylic acid) hydrogels fabricated by hydrogen bonding and Fe3+ ion cross-linking for cartilage tissue engineering - Kang, Min; Cheng, Yizhu; Hu, Yinchun; Ding, Huixiu; Yang, Hui; Wei, Yan; Huang, Di (Frontiers of materials science, 2023)
Autonomous self-healing hydrogels were achieved through a dynamic combination of hydrogen bonding and ferric ion (Fe 3+ ) migration. N,N ′-methylenebis (acrylamide) (MBA), a cross-linking agent, was added in this study. Poly(acrylic acid) (PAA)/Fe 3+ and PAA–MBA/Fe 3+ hydrogels were prepared by introducing Fe 3+ into the PAA hydrogel network. The ionic bonds were formed between Fe 3+ ions and carboxyl groups. The microstructure, mechanical properties, and composition of hydrogels were characterized by field emission scanning electron microscopy and Fourier transform infrared spectroscopy. The experimental results showed that PAA/Fe 3+ and PAA–MBA/Fe 3+ hydrogels healed themselves without external stimuli. The PAA/Fe 3+ hydrogel exhibited good mechanical properties, i.e., the tensile strength of 50 kPa, the breaking elongation of 750%, and the self-healing efficiency of 82%. Meanwhile, the PAA–MBA/Fe 3+ hydrogel had a tensile strength of 120 kPa. These fabricated hydrogels are biocompatible, which may have promising applications in cartilage tissue engineering.